A DSRM-Based Digital Library to Improve Reading Interest among Elementary School Students : MIN 7 Tulungagung Case Study - Zatadini, Galuh Indah; Rusydiyah, Evi Fatimatur; Vebrianto, Rian (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2025)
The low level of reading interest among Indonesian children reported by UNESCO to be merely 0.01% highlights an urgent need for innovative approaches to promote literacy engagement. The digital library emerges as a relevant solution; however, most existing services have not been specifically designed to cater to elementary school students. This study aims to develop a Digital Library based on the Design Science Research Methodology (DSRM) as a medium to enhance reading motivation among students at MIN 7 Tulungagung. The research employed the DSRM framework, encompassing the stages of problem identification, system design, prototype development, implementation, and evaluation. The primary users of the system were elementary school students, while validation involved expert review (validators) and direct user testing by students. Data collection techniques included observation, questionnaires, and documentation. The findings indicate that the developed Digital Library system achieved overall ratings in the “good” to “very good” categories. The user interface (UI) aspect obtained the highest score of 93.75%, followed by user compatibility (87.50%) and system functionality (87.50%). Conversely, data reliability and security received the lowest rating, at 75.00%. Implementation testing with students also demonstrated highly positive responses, with the indicator “Willing to use the application again” achieving a score of 95%. The students appeared enthusiastic, demonstrated independent use of the application, and exhibited increased motivation to read after exploring its features. In conclusion, the Digital Library developed using the DSRM approach has proven to be both feasible and effective in enhancing reading interest among elementary school students. Future work is recommended to strengthen data security mechanisms and expand the diversity of reading materials to further optimize the system’s contribution to children’s literacy development.